Construction jobsite management - Mincks, William R. (Delmar Pub., 1998)
This indispensable text takes the view of the commercial building contractor as it presents a detailed overview of job-site management. The comprehensive presentation discusses the entire process, including project relationships, shop drawings, documentation, safety management, project controls, software, and more.